Analyzed Perceptions Of The Poor Peoples On Health Promotion Program In Poverty Reduction Policy Program At Health Sector (Pkbk) Puskesmas Onohazumba District Onohazumba South Nias District In 2021 - Nirman Waruwu; Emi Girsang; Rapael Ginting; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
The Health Sector Poverty Reduction Program (PKBK) is a tangible manifestation of the onohazumba district south nias government's concern for the poor by providing comprehensive health service assistance, including the nutritional health promotion program. Research Objectives: To get an overview of the perceptions of the poor towards the nutrition health promotion program. Research Methods, This research instrument have data collection by in-depth interviews and observation of promotional activities carried out by the puskesmas. Data analysis is done by content analysis. Triangulation of sources to stakeholders, NGOs/journalists, health workers, and Public health posyandu cadres. Results: There are different perceptions of the nutritional health promotion program from various characteristics of the respondents. Economic factors are an obstacle for a person to behave healthily and affect the utilization of health services. The lack of media, the limited use of methods, the material presented is very short and not in-depth, the frequency and adequacy of financing for nutritional health promotion programs affect the effectiveness of nutritional health promotion programs. Conclusion: